2022
DOI: 10.1037/apl0000557
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of leadership and workplace safety: Examining relative importance, contextual contingencies, and methodological moderators.

Abstract: Given the high human and economic costs of workplace safety, researchers and practitioners have paid increasing attention to how leadership behaviors relate to workplace safety. Previous research has demonstrated that leadership behaviors are important for workplace safety. In this meta-analysis, we extend our understanding of the leadership-workplace safety relationship by (a) examining the associations between a broader range of five leadership categories-change-oriented, relational-oriented, task-oriented, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 129 publications
(306 reference statements)
2
22
0
Order By: Relevance
“…By doing so, this study extends the full‐range model of leadership (Bass, 1985) and highlights that employees may engage in transformational leadership. We also extend previous research that focused primarily on the role of vertical leaders in relation to workplace safety (e.g., Clarke, 2013; Lyubykh et al., 2022; Tucker et al., 2016; Zohar, Huang, Lee, & Robertson, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…By doing so, this study extends the full‐range model of leadership (Bass, 1985) and highlights that employees may engage in transformational leadership. We also extend previous research that focused primarily on the role of vertical leaders in relation to workplace safety (e.g., Clarke, 2013; Lyubykh et al., 2022; Tucker et al., 2016; Zohar, Huang, Lee, & Robertson, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Leadership behaviours represent one answer to this question. Researchers have focused on the role of leadership in employee safety for almost 50 years (e.g., Dunbar, 1975), and empirical findings consistently demonstrate the link between leadership and safety behaviours (Christian, Bradley, Wallace, & Burke, 2009; Clarke, 2013; Lyubykh et al., 2022; Nahrgang, Morgeson, & Hofmann, 2011). Transformational leadership, in particular, is considered one of the most effective leadership types in the context of workplace safety (e.g., Barling, Loughlin, & Kelloway, 2002; Clarke, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with early studies (Lee et al, 2020a,b;Lyubykh et al, 2022), power distance has been found to moderate leadership effectiveness. As such, leadership should be contingent according to culture.…”
Section: Moderators Power Distancesupporting
confidence: 84%